Scheduling Maintenance Activities During Planned Outages At Nuclear Power Plants - McKendall Jr, Alan R; Noble, James; Klein, Cerry (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
In order to maintain high production rates, electric power as well as manufacturing plants shut down so that maintenance activities can be performed on machines/equipment. These planned shut downs (outages) usually occur at least once a year and are more frequent for plants with older machines/equipment. The major costs associated with outages are cost of materials, labor cost, and loss of production cost. Due to high cost incurred from loss of production, the objective is to schedule maintenance activities such that outage duration is minimized. Since the resources required to perform maintenance activities are very limited, the problem of scheduling the maintenance activities is defined as a resource constrained project scheduling problem (RCPSP). In this paper, a solution technique, which consists of a simulated annealing heuristic, is presented for the RCPSP.